Pengaruh Metode Outdoor Learning terhadap Hasil Belajar IPS Siswa Kelas V SD Gugus II Kecamatan Bontoramba Kabupaten Jeneponto - Audrian Ahmad; Sudirman Sudirman; Muhammad Amin (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a quantitative research with a quasi-experimental research design.. The data analysis technique is descriptive statistical analysis and inferensial analysis using independent sample t-test. The result obtained in this study are: (a) there are differences in students’social studies learning outcomes between the experimental class and control class learning outcomes are higher than the control class, (b) there is a significant effect using the outdoor learning method on social studies learning outcomes. Student. The conclusion in this study is that there is an effect of using outdoor learning methods on social studies learning outcomes for fifth grade students of SD Gugus II, Bontoramba District, as evidenced by the results of the independent sample t-test with the results of the analysis obtained t count (7.064) > t table (2.0243).